2005
DOI: 10.1159/000083154
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Fluoride Concentrations in a Community without Water Fluoridation: Effects of Calcium and Use of a Fluoride or Placebo Dentifrice

Abstract: The results of a recent study by Whitford et al. [Caries Res 2002;36:256–265] with subjects whose drinking water was fluoridated led to two major conclusions: (1) Compared to the use of a placebo dentifrice, plaque fluoride concentrations ([F]) throughout much of the day are not significantly increased by the use of an F dentifrice but (2) they are positively related to plaque [Ca] (p = 0.0001). The present double-blind, double-crossover study with 16 subjects used the same protocol and was done to: (1) determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
2
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 46 publications
9
57
2
7
Order By: Relevance
“…This could have resulted in greater fluoride concentrations in saliva and in dental biofilm at 12 h or more after the last use of fluoride products, as compared with a relatively low baseline concentration. 30 The results of this study are in agreement with the findings of most of the studies conducted in areas with a fluoridated water supply. 13,20,21,22 These studies also did not show a long-term effect on the fluoride concentration in saliva and in dental biofilm compared to baseline values.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could have resulted in greater fluoride concentrations in saliva and in dental biofilm at 12 h or more after the last use of fluoride products, as compared with a relatively low baseline concentration. 30 The results of this study are in agreement with the findings of most of the studies conducted in areas with a fluoridated water supply. 13,20,21,22 These studies also did not show a long-term effect on the fluoride concentration in saliva and in dental biofilm compared to baseline values.…”
Section: Discussionsupporting
confidence: 91%
“…7,8,14,15,25,26,30 In these studies, fluoride measurements were taken on saliva samples collected 6-24 h after the regular daily use of fluoride products, brushing with a fluoride dentifrice, and/or using fluoride mouthrinsing. Most of these studies reported that the fluoride concentrations in saliva remained significantly elevated, over a period of 12-24 h, compared with the baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent increments in fluoride levels in the mouth reduce the mineral loss, thus reducing the progression of the caries. 4,10,11 Furthermore, studies 10,11 have shown that, in populations supplied with fluoridated water, the fluoride concentration on the plaque is not significantly increased over a large proportion of the day through the use of fluoridated toothpaste. Although the fluoride concentration on the plaque and in saliva increases abruptly during the use of a fluoridated toothpaste or a fluoridated mouthwash, it declines rapidly thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…An initial examination indicated that the data were not normally distributed. Thus, in order to normalize the data [Zero et al, 1992a;Vogel et al, 2000;Whitford et al, 2005], a logarithmic transformation of the salivary F levels was used prior to an analysis of variance test of the null hypothesis that there is no difference among the rinses in experiment 1. The Newman-Keuls multiple comparison test was then used on the transformed data to examine the effect of the rinses.…”
Section: Statistical Proceduresmentioning
confidence: 99%